Allocating the Burden of Proof in Medical Liability: A Comparative Perspective - Kvirkvia, Mariami (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2025)
This article examines the allocation of the burden of proof in medical liability. The paper is oriented toward a comparative law analysis, drawing on examples from various countries. It discusses The Concept of Proof and its Content, the Grounds for Allocating the Burden of Proof, and The Allocation of the Burden of Proof in American, German, and English Law, with particular attention to The Rule for Distributing the Burden of Proof in Medical Law, Reversing the Burden of Proof in Cases of Gross Medical Negligence, and Fully Controllable Risk as a Basis for Reversing the Burden of Proof. In this context, the legislation and judicial practice of both Continental and Anglo-American law countries are analyzed. The paper provides a detailed discussion of both statutory provisions and case law, as well as doctrinal debates, reflecting the specific challenges faced by plaintiffs in medical disputes. The study is enriched with examples from judicial practice, which give a practical dimension to the theoretical discussion and highlight the significance of judicial interpretations in shaping the doctrine of medical liability